Pengembangan Media Infografis untuk Meningkatkan Kemampuan Menganalisis Perubahan dan Keberlanjutan pada Pembelajaran Sejarah di SMK Kartika 1-2 Padang - Jasanddes, Febrialdo; Ofianto, Ofianto (Lembaga Yasin AlSys, 2025)
This study focuses on the development of instructional media in the form of infographics to enhance students’ analytical skills in understanding change and continuity in historical events. The research is motivated by the limited use of technology-based media in history education and the low level of students’ historical analysis skills. The aim of this study is to design, develop, and assess the feasibility, practicality, and effectiveness of infographic media for history learning at SMK Kartika 1-2 Padang. The method used is Research and Development (R&D) with the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The study involved 39 eleventh-grade students. Validation results from subject matter and media experts indicated that the developed infographics are highly feasible for use, with scores of 3.88 and 3.67, respectively. Practicality tests showed high scores from both students (3.68) and the teacher (3.44), suggesting that the media are highly practical in implementation. Effectiveness tests also yielded positive results, with scores of 3.72 from students and 3.29 from the teacher. These findings demonstrate that the developed infographic media are effective in improving students’ analytical abilities regarding change and continuity in historical events and can serve as an innovative alternative to support technology-integrated history learning.